Examining the relationship between cognitive flexibility and attitudes towards artificial ıntelligence technologies among students studying sports sciences - Damla Özsoy; Ozan Karakuş (Ozlem Book Center, 2023)
Cognitive flexibility and attitudes towards artificial intelligence technologies can be an indicator of how much sports educators can improve sports performance by revealing their potential to use these technologies effectively. This study aimed to examine the relationship between the attitudes towards artificial intelligence and cognitive flexibility of students studying in the field of sport sciences. It also focused on socio-demographic variables that may affect this relationship. The data obtained by quantitative research method were analyzed by descriptive statistics method using SPSS 29.0.1.0 (171) program. According to the results of the research, the attitudes towards artificial intelligence and cognitive flexibility levels of students who use technological devices more frequently during exercise and male students who exercise regularly were found to be higher than other students. In addition, it was observed that individuals who frequently use technological devices during exercise and who exercise regularly have higher attitudes towards artificial intelligence and cognitive flexibility. In addition, a statistically significant relationship was found between cognitive flexibility and artificial intelligence attitude. In the light of the findings, suggestions were presented to improve the skills and attitudes of sports education students in these areas.